2019
DOI: 10.1039/c8cp07158f
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis and its impact on characterization of mechanical properties of suspended monolayer molybdenum-disulfide sheets

Abstract: The hysteresis phenomenon frequently arises in two-dimensional (2D) material nanoindentation, which is generally expected to be excluded from characterizing the elastic properties due to the imperfect elastic behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…In theory, it can be caused by frictional behavior and plastic behavior, including the tip‐membrane friction, the membrane‐substrate friction, and the plastic deformation of the membrane. [ 17 ] Besides, the possibility of the large deformation of the tip should also be considered. Nevertheless, finite element simulations (shown in Figure S5, Supporting Information) demonstrated that only the elastic deformation would occur in the tip, excluding the influence of the deformation of the tip on the experimental results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In theory, it can be caused by frictional behavior and plastic behavior, including the tip‐membrane friction, the membrane‐substrate friction, and the plastic deformation of the membrane. [ 17 ] Besides, the possibility of the large deformation of the tip should also be considered. Nevertheless, finite element simulations (shown in Figure S5, Supporting Information) demonstrated that only the elastic deformation would occur in the tip, excluding the influence of the deformation of the tip on the experimental results.…”
Section: Resultsmentioning
confidence: 99%
“…Since stretching under out‐of‐plane displacement dominates the membrane deformation of these devices, AFM nanoindentation is more suitable for its accessibility to the investigation of the relationship between interlayer interaction and the mechanical properties under large out‐of‐plane deformation. Nevertheless, friction at the interface between the AFM tip and the membrane (called tip friction hereinafter for brevity) can induce the curve hysteresis during AFM nanoindentations [ 17 ] and further affect the effectiveness of the experimental results. [ 18,19 ] Besides, the characterization of the tip radius directly influences the measured fracture strength.…”
Section: Introductionmentioning
confidence: 99%
“…Nucleation and motion of domain walls separating such domains produces considerable dissipation of elastic strain energy, and the loading-unloading stress-strain curves demonstrate hysteresis loop [64]. Cyclic loading of suspended MoS 2 sheets during the nanoindentation experiments has also revealed the hysteresis behavior [65]. Damping properties of the compressed vertically aligned CNT brushes have been analyzed in [26].…”
Section: Introductionmentioning
confidence: 99%
“…This direction of application of an external force is most likely under real conditions since most of the fabricated nanoribbons are grown at the substrate, which is parallel to its layers. ,, Taking into account the low thickness of the layer and the fact that it is partially adhered to the substrate, we only act with force in the direction parallel to its layers. Most of the experiments , were carried out focusing only on examining such vertical forces. According to our simulations, the first three vibrational eigenmodes of the PNR have the following polarizations: mode 1 is horizontal, mode 2 is vertical, and mode 3 is horizontal.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, there are multiple possible approaches for simulating the mechanical behavior of nanostructures: ab initio DFT approach, force-field molecular dynamics, , FEM, or analytical solution of continuum models . Each of them has its own unique advantages, but the key factors are computational complexity and versatility in terms of nanomaterials.…”
Section: Resultsmentioning
confidence: 99%